IMPLEMENTATION OF EMPLOYMENT DOCUMENTS MANAGEMENT THROUGH REPOSITORY IN THE GOVERNMENT OF GORONTALO CITY - Sofyan Butolo; Arifin Tahir; Warno Panigoro (LP2M Universitas Bina Mandiri Gorontalo, 2021)
To find out the implementation of personnel document archiving management through a repository in the Gorontalo City Government, to find out the factors that determine the management of personnel document archives through a repository in the Gorontalo City Government Environment.This research uses a qualitative approach. Primary data was obtained through interviews with 11 informants/resource persons consisting of officials and employees as well as regional activity support staff who have duties in managing personnel document archives through repositories within the Gorontalo City Government.The results of this study indicate that the Implementation of personnel documents archival management through repositories in the Gorontalo City Government has been carried out by all regional apparatus organizations, by utilizing new media archives, namely electronic archives in the form of digital files which are transferred through the transfer of media archives, and continued. with electronic archive management then in the implementing personnel document archiving management through a repository within the Gorontalo City Government, there are factors that determine archival management activities, including facilities / infrastructure, Human Resources and Competence.